IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA DI SEKOLAH DASAR - Lala, Andi; Rohyana, Hadi (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The cultivation of character values in students from an early age is a crucial aspect in the effort to create a generation with noble morals and a strong sense of responsibility. This study aims to describe the implementation of character education through Scout extracurricular activities in elementary schools, as well as to identify the character values developed during its implementation. The research method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects included Scout leaders, teachers, and students in grades IV and V at SD Bani Saleh in Bekasi. The results of the study indicate that Scout extracurricular activities make a significant contribution to shaping students’ character. Activities such as flag ceremonies, educational games, outdoor exploration, and group work are effective in instilling values such as discipline, cooperation, responsibility, and leadership. Scout leaders play an active role in designing activities that align with the basic principles of Scouting and the values of character education. Supporting factors for successful implementation include support from the school, active student participation, and engaging, participatory methods of instruction. However, some obstacles remain, such as limited time and insufficient supporting facilities. Thus, Scout extracurricular activities in elementary schools can serve as a strategic means of supporting character education programs in a sustainable manner. This study recommends that Scouting activities continue to be developed and aligned with the needs and holistic development of students.